2015
DOI: 10.1038/srep16225
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical evaluation of an autologous living hyaline-like cartilaginous graft for articular cartilage repair: a pilot study

Abstract: In this pilot study, an autologous synthetic scaffold-free construct with hyaline quality, termed living hyaline cartilaginous graft (LhCG), was applied for treating cartilage lesions. Implantation of autologous LhCG was done at load-bearing regions of the knees in skeletally mature mini-pigs for 6 months. Over the course of this study, significant radiographical improvement in LhCG treated sites was observed via magnetic resonance imaging. Furthermore, macroscopic repair was effected by LhCG at endpoint. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…As mentioned above, the healthy articular cartilage is characterized by presenting a hyaline structure. Several authors have reported that using different current therapies for chondral lesions they have been able to obtain a hyaline-like repair tissue [139][140][141][142]. Thus, in this context, the basic question that is often asked regarding the cartilage regeneration after damage is about the role of all collagen types in the repair assessment, and the threshold to consider a regenerated cartilage as hyaline-like cartilage including ECM evaluation.…”
Section: Role Of Collagen Fibrils In the Quality Of Repaired Tissue In Chondral Defectsmentioning
confidence: 99%
“…As mentioned above, the healthy articular cartilage is characterized by presenting a hyaline structure. Several authors have reported that using different current therapies for chondral lesions they have been able to obtain a hyaline-like repair tissue [139][140][141][142]. Thus, in this context, the basic question that is often asked regarding the cartilage regeneration after damage is about the role of all collagen types in the repair assessment, and the threshold to consider a regenerated cartilage as hyaline-like cartilage including ECM evaluation.…”
Section: Role Of Collagen Fibrils In the Quality Of Repaired Tissue In Chondral Defectsmentioning
confidence: 99%
“…7 Methods for the full repair of hyaline cartilage (HC) and recovery of its structure and mechanical properties still have not been discovered. 6,8,9 The methods developed here are based on laser-induced modification of cartilage structure and the recognition of the key role the pores play in the normal functioning of the healthy avascular tissue. The term "pores" for the inhomogeneous tissues is considered as the areas of lesser density and stiffness providing pathways for the liquid mass transfer across the tissue, ensuring its proper nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they studied 3D stepwise chondrogenesis-mimicking ECM graft by controlling the stages of chondrogenic differentiation [12]. Our group has been studying porcine source ECM cartilage tissue engineering implants for years and developed Living Hyaline Cartilage Graft (LhCG) for cartilage tissue regeneration [13][14][15][16].…”
Section: Xenogeneic Extracellular Matrix (Ecm) Based Implants For Tismentioning
confidence: 99%
“…LhCG and dLhCG were engineered based on an established protocol in our previous publications as model xenografts [13][14][15][16]. dLhCG is a promising candidate for cartilage tissue engineering [17][18][19].…”
Section: Cell Membrane Coating On Graftsmentioning
confidence: 99%
See 1 more Smart Citation